THE EFFECT OF ONLINE CUSTOMER RATING, ONLINE CUSTOMER REVIEW, AND CASH ON DELIVERY (COD) PAYMENT SYSTEM ON PURCHASE DECISIONS AT TIKTOK SHOP - Apen Sintia; Henny Indrawat; M. Yogi Riyantama Isjoni (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The aim of this research is to determine the influence of online customer ratings, online customer reviews, and the cash on delivery (COD) payment system on purchasing decisions at the TikTok Shop. The population of this study were active undergraduate students majoring in Social Sciences Education, Faculty of Teacher Training and Education, Riau University who had shopped at the TikTok Shop. The sample in this study used a purposive sampling technique of 137 students. The method for collecting data uses a questionnaire that is distributed offline and the data collected is then tabulated and analyzed using multiple linear regression. Hypothesis testing is carried out using the F test and t test. Based on the research results, online customer ratings do not partially influence purchasing decisions, while online customer reviews and the cash on delivery (COD) payment system partially influence purchasing decisions. Then simultaneously online customer ratings, online customer reviews, and the cash on delivery (COD) payment system influence purchasing decisions at the TikTok Shop. Therefore, if TikTok Shop has a good online customer rating, online customer reviews, and there is a cash on delivery (COD) payment system, purchasing decisions will increase.